Closing the Induced Vehicle Travel Gap Between Research and Practice. Issue 1 (2017) - Milam, Ronald T.; Birnbaum, Marc; Ganson, Chris; Handy, Susan; Walters, Jerry
Several studies have rigorously documented the induced travel effect, in which added highway capacity leads to added vehicle travel. Despite the evidence, transportation planning practice does not fully account for this phenomenon, with the result that estimates of the potential congestion-reducing benefits of added highway capacity may be overstated and estimates of potential environmental impacts understated. In 2015, the California Department of Transportation (Caltrans) sponsored a review of applicable induced vehicle travel research that could inform transportation analysis guidance in response to new laws in California such as Senate Bill 743 (S.B. 743), which prohibits the use of vehicle level of service (LOS) and similar measures as the sole basis for determining significant transportation impacts under the California Environmental Quality Act. Instead, vehicle miles traveled was selected to replace LOS under S.B. 743, and along with the new metric there will be a requirement to account for induced travel effects in analysis of roadway capacity expansion projects. The Caltrans review revealed an inconsistent lexicon in academic research and among practitioners, questions about research applicability, limitations in the sensitivity of travel forecasting models, and confusion about the appropriate use of induced vehicle travel elasticities from research. This paper summarizes the Caltrans review and shares the findings to advance understanding of induced vehicle travel effects and suggest steps for additional research.